Cognitive aspects of disadvantaged entrepreneurs: Evidence from India. Issue 4 (8th August 2022) - Saleem, Imran; Yasir Arafat, Mohd; Balhareth, Hamad Hussain; Hussain, Amir; Dwivedi, Amit Kumar
ABSTRACT: Both entrepreneurs and community shape and shaped by each other. Understanding entrepreneurship in a community context has received much attention of the scholars. This research contributes to the community entrepreneurship literature by explaining drivers of entrepreneurial activities among disadvantaged community. Cognitive theoretical framework is used to hypothesize the relationship. A large sample of 1173 disadvantaged community people is used. The finding shows that attitude, role model, self-efficacy, social norms, and ability to recognize entrepreneurial opportunities positively encourage disadvantaged people of India to become entrepreneurs. Policy implications have been drawn and discussed to promote entrepreneurial activities amongst Indian disadvantaged community.